PENGARUH INTELLECTUAL CAPITAL TERHADAP PROFITABILITAS DAN DAMPAKNYA TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Abdul Halim; Hasan Basri; Faisal . (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2016)
This study aimed to study the effect of intellectual capital on profitability and its impact on stock prices. Profitability is proxied by ROE and EPS. Stock price is measured based on the average price of monthly stock at the time of the daily closing. The population in this study is the financial sector companies listed on the Indonesian Stock Exchange (BEI) in the period 2011-2014. The study looked at 47 issuers, using purposive sampling method by way of judgment sampling. Testing the hypothesis in this study using regression analysis and path analysis to see the path coefficients of each variable. The results showed that; (1) intellectual capital affect the profitability, (2) intellectual capital affect stock prices, (3) profitability affect stock prices, (4) intellectual capital, profitability affect stock prices.. Keywords: Intellectual Capital, Profitabilitas, ROE, EPS, Stock Price